Penerapan Strategi IMC Melalui Instagram @herstory.co.id dalam Meningkatkan Brand Awareness sebagai Media Online Perempuan - Filzah Zahrina; Abung Supama Wijaya (As-Syirkah: Islamic Economic & Financial Journal, 2025)
Social media has become a vital tool in building brand awareness in the digital era, particularly through visual platforms such as Instagram. This study aims to analyze the application of Integrated Marketing Communication (IMC) strategies by Herstory an Indonesian online media outlet focusing on women's empowerment, in enhancing brand awareness through its Instagram account @herstory.coid. A descriptive qualitative method was employed utilizing data collection techniques such as content observation, in-depth interviews with the media team, and analysis of secondary data. The findings reveal that Herstory consistently implements various IMC elements such as digital advertising (Instagram Ads), public relations, direct marketing (direct messages), and sales promotions (giveaways and brand collaborations) to strengthen its visibility and emotional connection with a female audience. These strategies have proven effective in building brand image and increasing audience engagement, although improvements are still needed in terms of consistency and diversification of communication channels. This study provides valuable insights for other online media in designing integrated and relevant marketing communication strategies in the digital age.